The Role of Family Education in Forming Children's Politeness in Mataram - Mas, Dzoharat Nabila (International Conference on Islamic Studies, 2021)
This study aimed to describe the role of family education and its relation to the children politeness in Mataram. This research study was motivated by the views of the researchers regarding the manners of children, especially teenagers, are now increasingly deteriorating. This deterioration of manners has afflicted almost all walks of life in Indonesia. It was not only an economic crisis, and crisis of confidence, but also crisis of morals and manners. This research was descriptive qualitative approach. This method was to reveal the reality and actuality of teenagers’ politeness from the roles performed by parents. In collecting of the data, I used three methods, namely the interview, observation, and also documentation method. Based on the research, the description of the role was obtained family education implemented by parents in Mataram was to instill belief values ​​in the form of faith and piety by using the method of habituation and exemplary, maintain and care for the physical and spiritual health of children, educate children with the method of reward and punishment, and educate children to have morals and good manners. The method of teaching education in the family has a role applied by the family was the formation of politeness to the children itself. This can be proven in the daily lives of children used good speech when talking to other people, respect others, and cherish younger people, as well respect elders.